Can the incidence of obstetric anal sphincter injury be reduced? The STOMP experience. (July 2016) - Basu, Maya; Smith, Dot; Edwards, Robin; ,
Abstract: Objective: To reduce the incidence of third and fourth degree perineal tears. Study design: This was a quality improvement project followed by an audit of outcomes. The population consisted of all women delivering vaginally over a 12 month period following implementation of the quality improvement measures. Following a review of clinical factors associated with all third and fourth degree tears over a 3 month period and a review of relevant evidence, a series of measures to try and reduce the incidence of such tears were introduced. These measures were collectively known as STOMP (Stop Traumatic OASIS Morbidity Project). These were adopted by all staff in our unit, with an accompanying programme of workshops and a publicity campaign to promote staff engagement. Data were collected on all third and fourth degree tears for a 12 month period following project launch. The primary outcome was the incidence of third and fourth degree perineal tears over a 12 month period. Results: There were a total of 3902 vaginal births during the 12 month period following project launch. Following full STOMP implementation, there was a significant decrease in the incidence of third/fourth degree tears (4.7% vs 2.2%, p < 0.0001). The reduction was most pronounced in the first 5 months (4.7% vs 1.51%, p < 0.0001). Conclusions: STOMP is a simple and low cost series of measures that has lead to a significant decrease in the incidence of third and fourth degree tears in this cohort of women.